Exposure to tritiated water at an elevated temperature: Genotoxic and transcriptomic effects in marine mussels (M. galloprovincialis). (November 2016) - Dallas, Lorna J.; Bean, Tim P.; Turner, Andrew; Lyons, Brett P.; Jha, Awadhesh N.
Abstract: Temperature is an abiotic factor of particular concern for assessing the potential impacts of radionuclides on marine species. This is particularly true for tritium, which is discharged as tritiated water (HTO) in the process of cooling nuclear institutions. Additionally, with sea surface temperatures forecast to rise 0.5–3.5 °C in the next 30–100 years, determining the interaction of elevated temperature with radiological exposure has never been more relevant. We assessed the tissue-specific accumulation, transcriptional expression of key genes, and genotoxicity of tritiated water to marine mussels at either 15 or 25 °C, over a 7 day time course with sampling after 1 h, 12 h, 3 d and 7d. The activity concentration used (15 MBq L −1 ) resulted in tritium accumulation that varied with both time and temperature, but consistently produced dose rates (calculated using the ERICA tool) of <20 Gy h −1, i.e. considerably below the recommended guidelines of the IAEA and EURATOM. Despite this, there was significant induction of DNA strand breaks (as measured by the comet assay), which also showed a temperature-dependent time shift. At 15 °C, DNA damage was only significantly elevated after 7 d, in contrast to 25 °C where a similar response was observed after only 3 d. The transcription profiles of two isoforms of hsp70, hsp90, mt20, p53 and rad51 indicated potential mechanisms behind this temperature-induced acceleration of genotoxicity, which may be the result of compromised defence. Specifically, genes involved in protein folding, DNA double strand break repair and cell cycle checkpoint control were upregulated after 3 d HTO exposure at 15 °C, but significantly downregulated when the same exposure occurred at 25 °C. This study is the first to investigate temperature effects on radiation-induced genotoxicity in an ecologically relevant marine invertebrate, Mytilus galloprovincialis . From an ecological perspective, our study suggests that mussels (or similar marine species) exposed to increased temperature and HTO may have a compromised ability to defend against genotoxic stress. Highlights: Marine mussels exposed to 15 MBQ L −1 tritiated water at 15 and 25 °C for 7 d. Genotoxicity and tissue-specific tritium accumulation varied with time and temperature. At 25 °C induction of DNA strand breaks occurred earlier than at 15 °C. Expression of key DNA repair genes increased after 3 d HTO exposure at 15 °C but decreased at 25 °C. Defence mechanisms potentially compromised in response to elevated temperature.